2002
DOI: 10.1007/s00270-001-0078-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interventional Radiology in the Treatment of Biliary Strictures Following Orthotopic Liver Transplantation

Abstract: Interventional radiology is an effective therapeutic alternative for the treatment of most biliary strictures complicating OLT. It has a high success rate and should be considered before surgical interventions. Elective surgery may be necessary in a few failed cases or those with more severe and extensive biliary strictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
2
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 16 publications
3
40
2
2
Order By: Relevance
“…However, the first results obtained with covered stents do not confirm these expectations yet. 4,25 Finally, a metal stent placement may be considered a complicating factor for further surgical procedures, because it can be difficult to remove because of ingrowth into the wall of the bile duct. 27,28 However, in general, Davidson et al 29 showed in a recent study of 80 patients that those who underwent conversion to CDJ after nonsurgical management of biliary complications appeared to have fewer postoperative complications than those who had an immediate surgical procedure.…”
Section: Choice In Treatment Of Bsmentioning
confidence: 99%
“…However, the first results obtained with covered stents do not confirm these expectations yet. 4,25 Finally, a metal stent placement may be considered a complicating factor for further surgical procedures, because it can be difficult to remove because of ingrowth into the wall of the bile duct. 27,28 However, in general, Davidson et al 29 showed in a recent study of 80 patients that those who underwent conversion to CDJ after nonsurgical management of biliary complications appeared to have fewer postoperative complications than those who had an immediate surgical procedure.…”
Section: Choice In Treatment Of Bsmentioning
confidence: 99%
“…Basic technique consists of a initial balloon biliopasty followed by long-term drainage, either endoscopic or percutaneous, during 1 year with frequent changes of drains or stents to avoid silent occlusions [51]. Duration of the long-term drainage is variable from one center to another, some choose to drain only during a short period of time after bilioplasty, but it requires more frequent treatment sessions (from one to three sessions) [53]. The success rate is approximately 70-80% in both endoscopic and percutaneous series and the rate of complications is similar (5-8%).…”
Section: Biliary Complicationsmentioning
confidence: 99%
“…In addition to these, the dose-area product (DAP) is an indicator of the total patient dose and can serve as a valuable tool for comparison. [3,4]. Il ricorso a procedure interventistiche in pazienti pediatrici sottoposti a trapianto di fegato (OLT, Orthotopic Liver Transplant) consente di affrontare in modo sicuro e poco invasivo le molte complicanze post-chirurgiche, evitando ai pazienti ulteriori interventi chirurgici [5,6].…”
Section: Introductionunclassified
“…Among minor biliary complications, the most common (6%-29%) is the formation of debris, stones and biliary sludge of varying severity [1,2]. Treatment for biliary complications, such as strictures of the biliodigestive anastomosis or lithiasis, by percutaneous biliary drainage and bilioplasty or by lithotripsy is successful in most cases, allowing resolution without surgical revision or repeat transplantation [3,4]. The use of interventional procedures in children who have undergone orthotopic liver transplantation (OLT) allows a safe and minimally invasive approach to many postoperative complications and spares the patients further surgical procedures [5,6].…”
Section: Introductionmentioning
confidence: 99%